Treatment with insulin analog X10 and IGF-1 increases growth of colon cancer allografts. - Henning Hvid; Marie-José Blouin; Elena Birman; Jesper Damgaard; Fritz Poulsen; Johannes Josef Fels; Christian Fledelius; Bo Falck Hansen; Michael Pollak (PLoS ONE, 2013)
Obesity and type 2 diabetes are associated with an increased risk for development of certain forms of cancer, including colon cancer. The publication of highly controversial epidemiological studies in 2009 raised the possibility that use of the insulin analog glargine increases this risk further. However, it is not clear how mitogenic effects of insulin and insulin analogs measured in vitro correlate with tumor growth-promoting effects in vivo. The aim of this study was to examine possible growth-promoting effects of native human insulin, insulin X10 and IGF-1, which are considered positive controls in vitro, in a short-term animal model of an obesity- and diabetes-relevant cancer. We characterized insulin and IGF-1 receptor expression and the response to treatment with insulin, X10 and IGF-1 in the murine colon cancer cell line (MC38 cells) in vitro and in vivo. Furthermore, we examined pharmacokinetics and pharmacodynamics and monitored growth of MC38 cell allografts in mice with diet-induced obesity treated with human insulin, X10 and IGF-1. Treatment with X10 and IGF-1 significantly increased growth of MC38 cell allografts in mice with diet-induced obesity and we can therefore conclude that supra-pharmacological doses of the insulin analog X10, which is super-mitogenic in vitro and increased the incidence of mammary tumors in female rats in a 12-month toxicity study, also increase growth of tumor allografts in a short-term animal model.